Proceedings from the conference Visibility and Collaboration of Researchers in Intercultural Communication in Finland - Visibilité et collaboration de la recherche en interculturel en Finlande - Suomela-Salmi, Eija; Dervin, Fred (fi=Turun yliopisto|en=University of Turku|, 2011)
This document contains papers that were presented at the conference “Enhancing the Visibility and Collaboration of Researchers in Intercultural Communication in Finland” which took place at the University of Turku (Finland), on October 1st & 2nd 2004. A paper version of some of the following papers as well as articles by specialists in intercultural communication will be published by Peter Lang.

Ce site rassemble les communications présentées à la conférence “Visibilité et collaboration de la recherche en interculturel en Finlande” qui s’est tenue à l’Université de Turku (Finlande), les 1er et 2 octobre 2004 Un ouvrage contenant une partie des communications qui suivent, ainsi que des articles écrits par des spécialistes de la communication interculturelle, sera publié par Peter Lang